2019
DOI: 10.1037/hea0000709
|View full text |Cite
|
Sign up to set email alerts
|

Moderation and mediation of the relationships between masculinity ideology and health status.

Abstract: Objective:The purpose of this study was to assess the direct and indirect relationships between the endorsement of traditional masculinity ideology (TMI) and self-reported health status through potential mediating variables of expectations of benefits from health risk behaviors and actual health risk behaviors. In addition, the objective was to test the moderating effect of gender identity, broadly defined (including cisgender and transgender men and women and nonbinary persons). Method: Participants (N ϭ 1233… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Previous research using the present data set (Levant et al, 2019) found that grouping of binary transgender and cisgender persons together by their shared gender identity resulted in commonality between such gender identity-matched groups. Specifically, it was found that gender identity defined as cisgender versus transgender did not moderate the relationship between masculinity beliefs and general health status, whereas gender identity defined as man or woman (regardless of sex assigned at birth) and nonbinary did.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Previous research using the present data set (Levant et al, 2019) found that grouping of binary transgender and cisgender persons together by their shared gender identity resulted in commonality between such gender identity-matched groups. Specifically, it was found that gender identity defined as cisgender versus transgender did not moderate the relationship between masculinity beliefs and general health status, whereas gender identity defined as man or woman (regardless of sex assigned at birth) and nonbinary did.…”
Section: Resultsmentioning
confidence: 62%
“…The data used in this study included only those participants whose data were retained after data cleaning procedures were performed (see Levant et al, 2019, for more information). A low level of missing data was observed (<.01% missing responses per item).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study uses data from a larger project, from which two manuscripts have been published and one is under review (Levant et al, 2019(Levant et al, , 2020(Levant et al, , 2021. None of these manuscripts examined measurement invariance by gender broadly conceived for the MRNI-SF, MRNI-VB, and the FIS-SF or compared mean scores on these scales across different gender identity groups.…”
Section: Methods Prior Use Of the Datamentioning
confidence: 99%
“…Masculinity ideologies have been operationalized as belief scales and often studied in the psychology of men and masculinities. Studies using these measures usually include men and women as informants, and more recently transgender and non-binary people as well (Levant et al 2019), because people of any gender have beliefs about how boys and men should think, feel and behave . Even more broadly, Whorley and Addis (2006, 656) argue, “when we study masculinity only in men we can easily fall prey to an implicit essentialism by failing to distinguish…[sex and gender]; thoroughly studying masculinity means understanding how it operates in the lives of both men and women.”…”
mentioning
confidence: 99%